Novel heterozygous mutation in alpha-2-macroglobulin (A2M) suppressing the binding of amyloid-β (Aβ) - Qiu, Guozhen; Cao, Liming; Chen, Yong-Jun (Frontiers in Neurology, 2023)
Introduction Many studies have suggested that the alpha-2-macroglobulin (A2M) gene may be involved in the pathogenesis of Alzheimer's disease (AD). A2M encoded by the A2M gene can specifically bind to the β-amyloid peptide and prevent fiber formation. Methods The patient in this study had progressive memory loss at the age of 60 years and underwent a series of neuropsychological tests, cranial magnetic resonance imaging (MRI), cerebrospinal fluid (CSF) biomarker analysis, and whole-exome sequencing (WES) to evaluate possible mutations. We used in silico tools and three-dimensional (3D) protein structure prediction to analyze the pathogenicity of the mutation and used a co-immunoprecipitation experiment to study the effect of mutations on amyloid-β (Aβ) binding. Results Based on neuropsychological tests, cranial MRI, and CSF biomarker analysis, the patient was diagnosed with AD. WES showed that there was a missense mutation in A2M (c.1229A>C, p.N410T). Bioinformatics analysis showed that this mutation was pathogenic. Moreover, 3D protein structure analysis showed that the A2M Asn410 residue was an N-glycosylation site, which was necessary for A2M activation to bind to Aβ. Missense mutations led to the loss of glycosylation at this site, which suppressed the binding of Aβ. The functional experiment also confirmed the prediction: the interaction between A2M and Aβ from the patient's plasma was weakened. Conclusions Our results demonstrate that this novel A2M p.N410T mutation may have a pathogenic role in AD, by altering the binding interactions between A2M and Aβ.